2012
DOI: 10.1177/1468087412468584
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for active diesel particulate filter regeneration based on late injection and exhaust recirculation with different fuels

Abstract: Wall flow–type particulate filters are used in diesel vehicle engines to reduce particulate emissions below the limits established in regulations Euro 5 and Euro 6. The soot accumulated in the trap is eliminated during regeneration processes, often combining passive strategies with active ones. Active regeneration is conducted by modifications of the engine control parameters with respect to those set for normal vehicle operation. In this work, three of these parameters were modified to look for an optimized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Also use of biodiesel may increase oil dilution. Lapuerta et al 8 studied the optimization of DPF regeneration strategies with different types of fuels. They concluded that the fuel properties are an important input, due to effects of the fuel on the combustion, on the thermal conditions and on the soot oxidation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Also use of biodiesel may increase oil dilution. Lapuerta et al 8 studied the optimization of DPF regeneration strategies with different types of fuels. They concluded that the fuel properties are an important input, due to effects of the fuel on the combustion, on the thermal conditions and on the soot oxidation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind this limitation for post-injected fuel mass rate is the reduction in O 2 concentration at the DPF inlet as the fuel mass increases, as observed in Figure 9. Very low O 2 concentration causes limitations to the chemical kinetics of the soot oxidation process [22]. These effects are more critical once the highest reactivity stage has finished, as observed in Figure 12.…”
Section: Active Regeneration Analysismentioning
confidence: 99%
“…Both parameters play a significant role in the properties of the exhaust gas arriving to the catalyst, mainly in terms of its temperature and the HC concentration [21]. In order to maximise the regeneration efficiency it is typical to combine the post-injection strategies with other engine control actuations, such as to act on the exhaust gas recirculation (EGR) valve, aimed at increasing the exhaust temperature [22] or the closure of the intake throttle valve, limiting the air flow coming into the cylinders in order to achieve richer equivalence ratio mixtures and higher HC concentration during the main combustion event [23]. Parks et al [24] studied the relationship between the exhaust gas temperature and the optimal post-injection timing for the regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Contamination by diesel soot has a significant impact on engine wear, with most engine manufacturers opting for Exhaust Gas Recirculation (EGR) technology to decrease NOx emissions. Returning exhaust product to the diesel engine combustion chamber may accelerate the degradation of the lubricant oil, affecting its rheological properties (George et al 2007;Aldajah et al 2007;Lapuerta et al 2014).…”
Section: Introductionmentioning
confidence: 99%